A computer simulation of kinetics in landing of gymnastics vaulting - Hao, W.-Y.; Li, X.-H.; Yu, J.-B.; Wu, C.-L. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
Gymnasts suffer from high impact loadings during landing and/or dismounts, and injuries are not unusual. The aims of this work were to develop a method for measuring or calculating the landing GRFs, which can be applied in practice and/or competitions, and to get loadings upon lower limbs during vaulting landings. A multi-body model with 19 segments and 52 freedoms was developed on the biomechanical simulation platform, software MSC.ADAMS / LifeMod. In order to test the validity of the model, the kinematics and simulation upon a university student`s drop jump were studied. The differences of maximum GRFs obtained from simulation studies and a force plate were less than 2.0% of the maximum GRF got by the force platform. After that, a vault performed by an elite gymnast was simulated and GRFs and net joint reaction forces and torques at ankle, knee, and hip were obtained.